2019
DOI: 10.1016/j.jcis.2018.08.109
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and application of sugarcane bagasse cellulose mixed esters. Part I: Removal of Co2+ and Ni2+ from single spiked aqueous solutions in batch mode using sugarcane bagasse cellulose succinate phthalate

Abstract: Sugarcane bagasse cellulose mixed ester succinate phthalate (SBSPh) was synthesized by a novel one-pot reaction method. The effects of temperature, time and mole fraction of succinic anhydride (χ) on the responses weight gain (wg), number of carboxylic acid groups (n), and adsorption capacity (q) of Co and Ni were evaluated by a 2 experimental design. The chemical structure of the material was elucidated by Fourier transform infrared, C Multiple Cross-Polarization solid-state NMR spectroscopy andH NMR relaxome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…All flasks (250 mL Erlenmeyers) containing C1 and solute solutions were stirred in an orbital shaker incubator (Model MA-830, Marconi), followed by a single filtration (C-41 (20 μm) filter paper) to separate the spent C1 adsorbent and the liquid phase. The liquid phases were analyzed by flame atomic absorption spectrophotometry (FAAS) (Model SpectrAA 50B, Varian) (λCu = 324.7 nm, λCr = 425.4 nm) for determination of the Cr(VI) and Cu(II) concentrations (Elias et al, 2019). The FAAS analyses were performed in triplicate.…”
Section: Adsorption Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…All flasks (250 mL Erlenmeyers) containing C1 and solute solutions were stirred in an orbital shaker incubator (Model MA-830, Marconi), followed by a single filtration (C-41 (20 μm) filter paper) to separate the spent C1 adsorbent and the liquid phase. The liquid phases were analyzed by flame atomic absorption spectrophotometry (FAAS) (Model SpectrAA 50B, Varian) (λCu = 324.7 nm, λCr = 425.4 nm) for determination of the Cr(VI) and Cu(II) concentrations (Elias et al, 2019). The FAAS analyses were performed in triplicate.…”
Section: Adsorption Experimentsmentioning
confidence: 99%
“…The experiments of adsorption and desorption were carried out using the experimental conditions described in Table 2. After desorption, C1 loaded with Cr(VI) or Cu(II) was recovered by single filtration, washed with an excess of ultrapure water, and dried in an oven at 80.0 ºC for 6 h (Elias et al, 2019). The other procedures were the same as described in Section 2.4.…”
Section: Desorption and Reuse Of Spent Adsorbentmentioning
confidence: 99%
“…e main advantage of these oxidized materials (SBox and Cox) comparing to other carboxylated materials prepared by our research group [14,15,20,22,[42][43][44][45] is that carboxylic acid functions in SBox and Cox are mainly from the oxidation of primary hydroxyl groups (R-CH 2 OH) of cellulose (in SB or Cel). On the contrary, when carboxylic acid groups are introduced in the Cel or SB through esteri cation reaction with cyclic carboxylic acid anhydrides, the application of esteri ed Cel or SB is limited to a pH range where the ester groups may not be easily hydrolyzed in the aqueous phase, e.g., 2-9 [46].…”
Section: Calculation Of Variation In Standard Free Energy Of Adsorptionmentioning
confidence: 99%
“…However, the other carboxyl functions bonded to the aromatic ring act as electron-withdrawing groups, due to both the inductive effect and the resonance effect, which increases the stability of the conjugated base (the carboxylate ion). This increases the acidity of at least two carboxylic acid groups (pK a,1 = 1.92, pK a,2 = 2.87, pK a,3 = 4.49, and pK a,4 = 5.63, in water at 25 ºC) (Dean & Lange 1999) of pyromellitic acid (a tetracarboxylic acid), compared to a As the main objective of this study was to synthesize an adsorbent able to remove both metal ions from aqueous solutions, the results obtained using the 2 3 experimental design indicated that the best synthesis condition should use the higher T level (100.0 ºC) and the lower t SA level (1.0 h). For the variable χ SA , the higher χ SA level favored Cu(II) adsorption, while the lower χ SA level favored Zn(II) adsorption.…”
Section: Evaluation Of the Effect Of Synthesis Conditions On The Adsorption Capacity Of Sbspy For Cu(ii) And Zn(ii)mentioning
confidence: 99%